1995
DOI: 10.2337/diab.44.12.1414
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Activation of CD8+ T-cell and CD8+ T-Cell Subsets in Patients With Newly Diagnosed IDDM

Abstract: Two- and three-color cytofluorimetric techniques were used to study the expression patterns of the activation antigen HLA-DR on peripheral blood immunoregulatory T-cells from 25 patients with newly diagnosed insulin-dependent diabetes mellitus (IDDM) and 14 age- and sex-matched control subjects. The mean percentage of total activated (CD3+HLA-DR+) T-cells was significantly elevated in the IDDM group compared with the control group (P < 0.001). In control subjects, basal activation of CD4+ and CD8+ lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
3
13
2
Order By: Relevance
“…Aberrant activation of CD8 cells in patients with newly diagnosed insulin-dependent diabetes mellitus was reported pre- (16). It has also been shown that type 1 diabetes of long standing is associated with activation of circulating T cells (9), corroborating our findings of increased activated T-cell phenotypes during the natural course of the disease, as shown in the placebo group.…”
Section: Discussionsupporting
confidence: 81%
“…Aberrant activation of CD8 cells in patients with newly diagnosed insulin-dependent diabetes mellitus was reported pre- (16). It has also been shown that type 1 diabetes of long standing is associated with activation of circulating T cells (9), corroborating our findings of increased activated T-cell phenotypes during the natural course of the disease, as shown in the placebo group.…”
Section: Discussionsupporting
confidence: 81%
“…The same applies to the observation of more marked HLA-DR expression on CD4 ϩ cells in DML, which seems to be restricted to memory cells, whereas at manifestation of IDDM it occurs in both memory (27) and naive T cells (27,28). HLA-DR expression was, however, not restricted to the CD45RA Ϫ compartment (21) of CD8 ϩ cells in DM, but, rather, favored the CD45RA ϩ subset.…”
Section: Discussionmentioning
confidence: 81%
“…ϩ T cells and their CD45RA ϩ subsets in patients with newly manifested IDDM than in HS (27,28 addition, a significantly greater expression of the early activation antigen CD69 is observed in DML than DM, but not vs. HS on CD4 ϩ (ϩ48%) and CD8 ϩ T cells (ϩ40%). This contrasts with the increased proportion of CD69 ϩ cells described among peripheral blood lymphocytes vs. HS in a group of 12 patients with DM and DML (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes differences, compared to healthy controls, in the proportion of T cells (alKassab & Raziuddin, 1990;Ilonen et al, 1991;Petersen et al, 1996) and also in their function (Hehmke et al, 1995;Spatz et al, 2003). In particular, there has been much conjecture over the frequency and function of Treg in T1D .…”
Section: Failure Of Immunological Tolerance In Human T1dmentioning
confidence: 99%